Comparison of Serum and Salivary CRP Levels with Leukocyte Parameters in Dogs with Canine Parvoviral Enteritis - Ölmez, Gaye; Çakar, Ceren; Turan, Mahmut; Gülersoy, Erdem (Kastamonu Üniversitesi, 2025)
Aim to study: Canine parvovirus (CPV) is a highly contagious cause of enteritis, associated with high morbidity, mortality, and low survival rates in untreated dogs. While severe disease primarily affects younger dogs, immunocompromised adults may also be susceptible. Since the clinical signs of CPV infection are nonspecific, reliable biomarkers are essential for differential diagnosis and disease severity assessment. This study aimed to evaluate the correlation between serum and salivary C-reactive protein (CRP) levels in dogs with parvoviral enteritis (PVE) and their association with complete blood count (CBC) parameters. Additionally, we sought to highlight the clinical relevance of saliva as an alternative diagnostic fluid, reducing the need for frequent blood sampling and minimizing stress in affected animals. Material and methods: A total of 20 dogs (10 healthy controls, 10 with PVE) underwent physical and laboratory examinations, including CBC and serum and salivary CRP measurements. Results: In the PVE group, WBC, monocyte, granulocyte, MCH, and MCHC levels were significantly lower (P < 0.020), whereas serum and salivary CRP levels were markedly elevated (P < 0.000). ROC analysis demonstrated the outstanding diagnostic performance of serum and salivary CRP levels (AUC > 0.900). Moreover, a very strong positive correlation was observed between serum and salivary CRP concentrations (r = 0.912). Conclusion: These findings suggest that salivary CRP, like serum CRP, may serve as a valuable biomarker for assessing disease severity in CPV cases where blood collection is challenging. However, further studies are needed to confirm its diagnostic and prognostic reliability, considering factors such as dilution and salivary flow rate.
Keywords: Veterinary Sciences (Other); Veteriner Bilimleri (Diğer)